2022
DOI: 10.1007/s12028-022-01565-5
|View full text |Cite
|
Sign up to set email alerts
|

Processed Electroencephalogram-Based Monitoring to Guide Sedation in Critically Ill Adult Patients: Recommendations from an International Expert Panel-Based Consensus

Abstract: Background The use of processed electroencephalography (pEEG) for depth of sedation (DOS) monitoring is increasing in anesthesia; however, how to use of this type of monitoring for critical care adult patients within the intensive care unit (ICU) remains unclear. Methods A multidisciplinary panel of international experts consisting of 21 clinicians involved in monitoring DOS in ICU patients was carefully selected on the basis of their expertise in neurocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 103 publications
(172 reference statements)
0
17
0
Order By: Relevance
“…This represents a critical knowledge gap, limiting the routine use EEG-guided sedation in the ICU. 8 A large retrospective study that related comorbidity-dependent changes in EEG responses to anesthetics in the operating room found that a wide range of comorbidities was associated with decreased alpha power. 9 Our case supports this growing evidence base and helps translate it to ICU use with finer temporal resolution and a within-subject paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…This represents a critical knowledge gap, limiting the routine use EEG-guided sedation in the ICU. 8 A large retrospective study that related comorbidity-dependent changes in EEG responses to anesthetics in the operating room found that a wide range of comorbidities was associated with decreased alpha power. 9 Our case supports this growing evidence base and helps translate it to ICU use with finer temporal resolution and a within-subject paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…In the ICU, the use of EEG-based monitors is controversial and the evidence is still scarce. However, recent consensus had recommended its use to monitor the level of sedation in all patients unsuitable for clinical evaluation (43). In neurocritical patients, a beneficial impact of BIS-guided sedation in addition to a clinical scale-guided protocol was reported (44).…”
Section: Discussionmentioning
confidence: 99%
“…5). Some centers use processed electroencephalography devices to help guide sedation administration to avoid over- and under-sedation, especially with concomitant neuromuscular blockade (85). If the underlying cause is driven by DDI, both agents should be stopped, and a decision made as to whether either should be resumed or replaced.…”
Section: Methodsmentioning
confidence: 99%